Tıbbi Terminoloji (Vaka Örnekli) - Topal Önal, Harika; Aluçlu, Mustafa Arif; Aksak , Tiinçe; Kundakçı, Emre; Aşkın, Ali; Oktay Gültekin, Efdal; Delialioğlu, Nuran; Gökçe , Esma; Bozkurt, Abdi; Arslan, Sevban; Yeşil Bayülgen, Melek; Bayülgen, Abdulkerim; et al. (Akademisyen Yayınevi Kitap DOI Portalı, 2023)
-